A U-Box Type E3 Ubiquitin Ligase Prp19-Like Protein Negatively Regulates Lipid Accumulation and Cell Size in Chlamydomonas reinhardtii - Luo, Qiulan; Zhu, Hui; Wang, Chaogang; Li, Yajun; Zou, Xianghui; Hu, Zhangli (Frontiers in Microbiology, 2022)
Microalgae lipid triacylglycerol is considered as a promising feedstock for national production of biofuels. It becomes a hotspot issue how to increase TAG content and productivity of microalgae in the study of biodiesel. Precursor RNA processing protein (Prp19) which is the core component of eukaryotic RNA splice NTC (nineteen associated complex), plays important roles in the mRNA maturation process in eukaryotic cells, has variety functions in cell development, and is even directly involved in the biosynthesis of oil bodies in mouse. Nevertheless, its function in Chlamydomonas reinhardtii remains unknown. Here transcriptional levels of CrPrp19 under nutrition deprivation were analyzed, and both RNA interference and overexpressed transformants were constructed. The expression level of CrPrp19 was suppressed by nitrogen and sulfur deficiencies. Cells densities of CrPrp19 RNAi lines decreased, their neutral lipid contents increased to 1.33 and 1.34 times over those of controls. The cells of CrPrp19 RNAi lines were larger and more resistant to sodium acetate than control. Considerably none of the alteration in growth or lipid contents was found in the CrPrp19 overexpression transformants than wild type. Fatty acids were also significantly increased in CrPrp19 RNAi transformants. Subcellular localization and Y2H analysis showed that CrPrp19 was a nuclear protein, which is involved in cell cycle regulation. In conclusion, CrPrp19 protein was necessary for negatively regulating lipid enrichment and cell size, but not stimulatory for lipid storage.